We have to find the derivative of y = (x+3)^2 + 2(x+3)(x-4) + (x-4)^2

y = (x+3)^2 + 2(x+3)(x-4) + (x-4)^2

Use the relation [x^n]' = n*x^(n - 1) and the chain rule

y' = 2( x + 3) + 2*( x + 3) + 2* ( x - 4) + 2*(x - 4)

=> 2x + 6 + 2x + 6 + 2x - 8 + 2x - 8

=> 8x - 4

**The required derivative is 8x - 4**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.